Novel Leu-Val Based Dipeptide as Antimicrobial and Antimalarial Agents: Synthesis and Molecular Docking - Ezugwu, James A.; Okoro, Uchechukwu C.; Ezeokonkwo, Mercy A.; Bhimapaka, China R.; Okafor, Sunday N.; Ugwu, David I.; Ekoh, Ogechi C.; Attah, Solomon I. (Frontiers in Chemistry, 2020)
The increase of antimicrobial resistance (AMR) and antimalarial resistance are complex and severe health issues today, as many microbial strains have become resistant to market drugs. The choice for the synthesis of new dipeptide-carboxamide derivatives is as a result of their wide biological properties such as antimicrobial, anti-inflammatory, and antioxidant activities. The condensation reaction of substituted benzenesulphonamoyl pentanamides with the carboxamide derivatives using peptide coupling reagents gave targeted products (8a-j). The in silico antimalarial and antibacterial studies showed good interactions of the compounds with target protein residues and a higher dock score in comparison with standard drugs. In the in vivo study, compound 8j was the most potent antimalarial agent with 61.90% inhibition comparable with 67% inhibition for Artemisinin. In the in vitro antimicrobial activity, compounds 8a and 8b (MIC 1.2 × 10−3 M and 1.1 × 10−3 M) were most potent against S. aureus; compound 8a, 8b, and 8j with MIC 6.0 × 10−3 M, 5.7 × 10−4 M, and 6.5 × 10−4 M, respectively, were the most active against B. subtilis; compound 8b (MIC 9.5 × 10−4 M) was most active against E.coli while 8a, 8b and 8d were the most active against S. typhi. Compounds 8c and 8h (MIC 1.3 × 10−3 M) each were the most active against C. albicans, while compound 8b (MIC 1.3 × 10−4 M) was most active against A. niger.